Investors' reactions to international joint venture announcements - Tan, Ying Zi (Nanyang Technological University, 2012)
This study examines investors’ reactions towards joint venture announcements by publicly-listed firms in Singapore. We are interested to find out whether investors react differently to domestic and international joint venture announcements. In addition, we investigate how this relationship is influenced by the parent firm’s corporate governance variables such as the presence of fund institutional investors, proportion of independent directors, presence of performance-based compensation and presence of family-influenced board at the time of joint venture announcements. Based on a sample of 143 firms listed on the Singapore Exchange (SGX), we first established that firms which announce joint ventures experience positive abnormal returns on average. Subsequent regression analysis reveals that firms which announce international joint ventures have lower abnormal returns when compared with firms which announce domestic joint ventures. This negative association is weakened when there is the presence of fund institutional investors and family-influenced board. We did not find any significant effect of a firm’s proportion of independent directors and presence of performance-based compensation on this negative association. This is contrary to our theoretical predictions and led us to question the effectiveness of such corporate governance tools when studying investors’ reactions to international joint venture announcements.